Pemberdayaan istri nelayan Kelurahan Samataring melalui program daur ulang sampah plastik - Muhammad Syukur; A. Octamaya Tenri Awaru; Zainal Arifin (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The Community Partnership Program (PKM) partner is the Fisherman's Wife in Samataring Village. The problems are: (1) lack of awareness of fishermen's wives about the importance of cleanliness and ways to deal with waste, (2) lack of understanding of housewives of fishermen's wives if the waste can be effective and valuable, (3) lack of understanding and knowledge and skills of mothers- housewives of fishermen wives on how to recycle plastic waste is very minimal due to lack of training and socialization related to recycling plastic waste, and (4) the amount of free time is wasted because there is no productive activity that can be done. External targets are plastic waste that is recycled into economic value items such as lanterns, plastic flowers and brooches. The method used is: lecture, demonstration, direct practice. The results achieved are (1) partners have the importance of cleanliness and how to cope with waste, (2) partners have an understanding if waste can be effective and valuable, (3) partner skills in recycling waste into goods that are efficient and valuable, (4) partners become more productive in utilizing their free time.